Internal Conflicts in Muslim Societies - Shah, Ashiq Ali (Intellectual Discourse, 2013)
An analysis of psychological theories and the social dynamics of the society help identify salient attributes and processes relevant to conflict among Muslims. The psychodynamic concept of personality and frustration-aggression hypothesis account for the socialization practices in the Muslim societies, emotional instability, unfavorable evaluation of those holding a different viewpoint and venting out one’s aggression on the weaker. The tendency of the Muslims to praise their sect/tribe/religious group leads to a groupthink situation that polarizes intergroup relationships. The acts of categorization in group and out group, as postulated by the social identity theory, contribute towards the distorted perception of each other. The Islamic notions of brotherhood, unity and ethnic identity as means of personal identification and social interaction seems to have been forgotten by the Muslims. Though the Western social-psychological constructs are helpful in understanding the causes of conflict among Muslims, they are not germane to Muslim societies. The group belongingness and group favouritism is not necessarily a tool of discrimination and conflict but is an essential component of one’s survival in a collectivist society. The Western theories also do not address the economic and political circumstances responsible for the multitude of conflicts among Muslims.